2016
DOI: 10.1007/s40722-016-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

Air turbine optimization for a bottom-standing oscillating-water-column wave energy converter

Abstract: The oscillating-water-column wave energy device equipped with an air turbine is widely regarded as the simplest and most reliable, and the one that was object of the most extensive development effort. The aerodynamic performance of the air turbine plays a major role in the success of the technology. A case study was selected to investigate these issues: the existing bottom-standing plant on the shoreline of the island of Pico, in Azores Archipelago. The overall performance of the OWC plant was modelled as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Eq. (10) is essentially the same as the differential equation for pressure fluctuations in [27], derived in a similar line of reasoning and used for 2D and 3D cases.…”
Section: Linear Analysismentioning
confidence: 98%
“…Eq. (10) is essentially the same as the differential equation for pressure fluctuations in [27], derived in a similar line of reasoning and used for 2D and 3D cases.…”
Section: Linear Analysismentioning
confidence: 98%
“…With this type of hypothesis on the air pressure inside the chamber, it is possible to find in ocean engineering literature an evolution equation governing the dynamics the pressure variation P ch (t). For instance, we refer to [11,15]. It is derived for oscillating water column with Wells turbines [29], for which the relation between the pressure drop and the velocity of the air in the resistance layer is linear.…”
Section: Air Pressure Dynamicsmentioning
confidence: 99%
“…In the last decades oscillating water columns have been widely investigated both experimentally and numerically in the hydrodynamical engineering literature for the sake of understanding how to increase the performance of these wave energy converters in order to facilitate a real installation. For instance, we refer to [11,14,15,24,30,31,32] and references therein. In particular, in [30] Rezanejad, Bhattacharjee and Soares showed that the inclusion of an artificial step at the sea bottom may lead to a significantly increased efficiency, that is the capacity of power absorption of a wave energy converter.…”
mentioning
confidence: 99%
“…Numerical and physical studies on a coast/breakwater-integrated OWC can be found in Morris-Thomas, Irvin & Thiagarajan (2007), He, Huang & Law (2012), Zhang, Zou & Greaves (2012), López & Iglesias (2014), Elhanafi et al. (2016), Falcão, Henriques & Gato (2016), López et al. (2016), He, Leng & Zhao (2017) and Howe & Nader (2017).…”
Section: Introductionmentioning
confidence: 99%